(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Proof of rape depends not only in the physical findings of the victims but also to the subjective intentions of the assailants. Objective: The purpose of the present study was to find out the medicolegal findings of rape victims in order to point out the visible loopholes of the procedure. Methodology: This was a cross sectional descriptive type of study which was done in the Dept. of Forensic Medicine, Dhaka Medical College, Dhaka, Bangladesh from January to December 2016 with maintaining ethical issues. Rape cases from 23 police stations of Dhaka Metropolitan area were sent for medicolegal examination and victims who ultimately agreed to do medicolegal examinations were examined and opinions were given regarding the issues. Results: A total number of 69 cases from 23 police stations of Dhaka Metropolitan area were studied. In this study, majority (70.0%) of the victims was within 11 to 20 years of age and 65.0% of the victims were unmarried. Almost 68.0% of the victims were examined within 7 days followed by 32.0% of the victims after 7 days to beyond one month after rape; however, 48.0% of the victims showed sign of recent hymeneal tear with bruise and abrasion followed by 52.0% showed sign of old hymeneal tear. Spermatozoa were not found in any of the specimen of high vaginal swab. Conclusion: In conclusion, teenage unmarried girl are the most common victim of rape cases. Journal of National Institute of Neurosciences Bangladesh, 2017;3(2): 106-109